Refusing to wait: Hunger-striking in the age of Gazafication - Abo-Basha, Ayah (AUC Knowledge Fountain, 2018)
What happens when six months of waiting become six more and six more, always arbitrarily and uncertainly? And, in turn, what happens when people refuse to wait? I address this question by tracing how Palestinian prisoners refuse to wait in detention by increasingly resorting to individual "freedom strikes" since 2011 to demand their release. This mode of striking is contrasted to the strike of 2004: the last general collective hunger-strike demanding improved prison conditions' which was the predominant mode of hunger-striking before Oslo. I trace how freedom-strikers' shift towards targeting administrative detention is a refusal not only of their own arbitrarily renewable detention periods, but also of Israel's new mode of governing at large post-Oslo: when negotiations became permanent therein inscribing a shift from "waiting for" towards "waiting to wait". This shift was further enabled by Israel's intensified individuation practices and closure technologies after the Second Intifada' the result of which effectively repressed what was ingrained as the collective model of "doing politics" in the social imaginary: the structure of nationalist factions and tantheemat (political organizations). This thesis moves beyond a simplistic portrayal of how individuation technologies divide collectives and discipline people into good subjects who wait crises out. Instead, it explores how the individual freedom-striker stubbornly forges new terrains of struggle where former collectives, organized into the logic of nationalist parties and factions, no longer hold; how individual bodies emerged, one after the other, out of the void of hunger-strikes between the last general collective strike in 2004 and the string of individual freedom strikes beginning in 2011 to craft a different mode of collectivity and sculpt potentialities beyond the time-space of waiting to wait. This thesis situates prisons as a site that is generative of such potentialities, and traces such reconfiguring and reassembling of new collectivities within the fields and assemblages of hunger in contemporary Palestine.